Implementasi Modul Aturan Cramer dan Invers Matriks pada Materi Katrol Tetap dalam Meningkatkan Hasil Belajar Fisika Siswa - Purwanti, Nurul Yunda Nanik; Dina Maharika; Supriadi, Bambang; Anggraeni, Firdha Kusuma Ayu; Ernasari, Ernasari (U-Teach: Journal Education of Young Physics Teacher, 2025)
The low learning outcomes of students in physics lessons are one of the main challenges in education. One of the reasons behind this low achievement is the lack of teaching materials available in schools. The purpose of this research is to improve student learning outcomes for the implementation of learning modules at SMA Negeri Arjasa. This type of research is quantitative descriptive with a One Group Pretest-Posttest Design. The sample used was 60 students. The results showed that in class XI 2 that applied the Cramer rule, the average posttest result was 84.87 and the pretest result was 49.53. A similar thing was found in class XI 4 with an average posttest result of 86.9 which was better than the pretest result of 55.8. The increase was analyzed using the N-Gain Score through SPSS 25 to get an average of 0.7 including the high category. The learning outcomes of students who applied Cramer's rule and the inverse matrix method showed a better improvement compared to the learning outcomes of students before being treated with both methods in solving fixed pulley problems